Avian flu & profit margins - Abd Razak, Dzulkifli (2005)
IT looks like the world will be no longer be safe in the years ahead. The threat of war and violence will continue to be a feature of the new millennium with Palestine, and now Iraq, as the crucibles of insurgency. This has been acknowledged recently by London’s former ambassador to Washington when he said the Iraq war fuelled terrorism. It is bound to spread to other frontiers in the region depending on how the cards are stacked. What is certain, however, is the threat from the avian flu that is now extending its geographical reach beyond the Asian borders into Europe and possibly the Americas. So far, more than 100 known cases have occurred in Southeast Asia and at least 60 have died in Cambodia, Indonesia, Thailand and Vietnam.